2024
DOI: 10.3390/ijms25021213
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Exercise Intensity on Cerebral BDNF Levels: Role of FNDC5/Irisin

Clémence Leger,
Aurore Quirié,
Alexandre Méloux
et al.

Abstract: The positive effects of physical exercise (EX) are well known to be mediated by cerebral BDNF (brain-derived neurotrophic factor), a neurotrophin involved in learning and memory, the expression of which could be induced by circulating irisin, a peptide derived from Fibronectin type III domain-containing protein 5 (FNDC5) produced by skeletal muscle contraction. While the influence of EX modalities on cerebral BDNF expression was characterized, their effect on muscle FNDC5/Irisin expression and circulating iris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…BDNF is believed to play a key role in brain development and maintenance [30]. Compared to other members of the growth neurotrophic factor family, BDNF is highly expressed in the cerebral cortex and hippocampus [31]. It has been shown that BDNF promotes neuroplasticity and facilitates synaptic transmission, dendritic modification, receptor trade, and long-term potentiation [30].…”
Section: Introductionmentioning
confidence: 99%
“…BDNF is believed to play a key role in brain development and maintenance [30]. Compared to other members of the growth neurotrophic factor family, BDNF is highly expressed in the cerebral cortex and hippocampus [31]. It has been shown that BDNF promotes neuroplasticity and facilitates synaptic transmission, dendritic modification, receptor trade, and long-term potentiation [30].…”
Section: Introductionmentioning
confidence: 99%